Pengaruh Kegiatan Herbarium Terhadap Perkembangan Kreativitas Anak di PAUD Kasih Ibu I Luar Parit - Endang Susri Ranti; Nur Hazizah (Universitas Trunojoyo Madura, 2019)
The purpose of this study was to determine the creativity development of children 5-6 years old with herbarium activities in PAUD Kasih Ibu I Luar Parit. The creativity development activities in the field use dry leaf collage activities and serveral other activities such as drawing coloring, and forming fruits from plasticine. But the work produced is almost exactly the same as the teacher’s example. Through this herbarium activity researhers want to see the creativity development of children 5-6 years. Quantitative reasearch with experimental methods in the form of quasi experimental is a method in this study. All children in PAUD Kasih Ibu I Luar Parit totaling 34. Group B1 experimental sample and B2 control sample with 12 children each class. Purposive sampling. As for the technique of collecting data using deed test and oral test.statement instrumen grid is used as a data collection tool. The results of the average experimental 77,77 and the control 70,83. So the use of herbarium activities had a significant effect on the development of creativity of children 5-6 years old at the PAUD Kasih Ibu I Luar Parit academic years 2018/2019.